Welcome to Westonci.ca, the ultimate question and answer platform. Get expert answers to your questions quickly and accurately. Connect with a community of experts ready to help you find accurate solutions to your questions quickly and efficiently. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
To solve the system of linear equations:
[tex]\[ \begin{cases} x + y = 4 \\ 2x + 3y = 0 \end{cases} \][/tex]
we will follow a step-by-step approach.
### Step 1: Express one variable in terms of the other.
From the first equation, [tex]\(x + y = 4\)[/tex], we solve for [tex]\(x\)[/tex]:
[tex]\[ x = 4 - y \][/tex]
### Step 2: Substitute this expression into the second equation.
We substitute [tex]\(x = 4 - y\)[/tex] into the second equation, [tex]\(2x + 3y = 0\)[/tex]:
[tex]\[ 2(4 - y) + 3y = 0 \][/tex]
### Step 3: Simplify the equation and solve for [tex]\(y\)[/tex].
First, distribute the 2:
[tex]\[ 8 - 2y + 3y = 0 \][/tex]
Combine like terms:
[tex]\[ 8 + y = 0 \][/tex]
Solve for [tex]\(y\)[/tex]:
[tex]\[ y = -8 \][/tex]
### Step 4: Substitute the value of [tex]\(y\)[/tex] back into the expression for [tex]\(x\)[/tex].
Now, substitute [tex]\(y = -8\)[/tex] back into the equation [tex]\(x = 4 - y\)[/tex]:
[tex]\[ x = 4 - (-8) \][/tex]
[tex]\[ x = 4 + 8 \][/tex]
[tex]\[ x = 12 \][/tex]
### Conclusion
The solution to the system of equations is [tex]\(x = 12\)[/tex] and [tex]\(y = -8\)[/tex].
Thus, the correct answer is:
[tex]\[ \boxed{D. \, x = 12, \, y = -8} \][/tex]
[tex]\[ \begin{cases} x + y = 4 \\ 2x + 3y = 0 \end{cases} \][/tex]
we will follow a step-by-step approach.
### Step 1: Express one variable in terms of the other.
From the first equation, [tex]\(x + y = 4\)[/tex], we solve for [tex]\(x\)[/tex]:
[tex]\[ x = 4 - y \][/tex]
### Step 2: Substitute this expression into the second equation.
We substitute [tex]\(x = 4 - y\)[/tex] into the second equation, [tex]\(2x + 3y = 0\)[/tex]:
[tex]\[ 2(4 - y) + 3y = 0 \][/tex]
### Step 3: Simplify the equation and solve for [tex]\(y\)[/tex].
First, distribute the 2:
[tex]\[ 8 - 2y + 3y = 0 \][/tex]
Combine like terms:
[tex]\[ 8 + y = 0 \][/tex]
Solve for [tex]\(y\)[/tex]:
[tex]\[ y = -8 \][/tex]
### Step 4: Substitute the value of [tex]\(y\)[/tex] back into the expression for [tex]\(x\)[/tex].
Now, substitute [tex]\(y = -8\)[/tex] back into the equation [tex]\(x = 4 - y\)[/tex]:
[tex]\[ x = 4 - (-8) \][/tex]
[tex]\[ x = 4 + 8 \][/tex]
[tex]\[ x = 12 \][/tex]
### Conclusion
The solution to the system of equations is [tex]\(x = 12\)[/tex] and [tex]\(y = -8\)[/tex].
Thus, the correct answer is:
[tex]\[ \boxed{D. \, x = 12, \, y = -8} \][/tex]
We hope this was helpful. Please come back whenever you need more information or answers to your queries. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.